Early markers of Fabry disease revealed by proteomics1. Issue 6 (19th June 2015) - Matafora, V.; Cuccurullo, M.; Beneduci, A.; Petrazzuolo, O.; Simeone, A.; Anastasio, P.; Mignani, R.; Feriozzi, S.; Pisani, A.; Comotti, C.; Bachi, A.; Capasso, G.
<x xml:space="preserve">Abstract</x> Discovery of early urinary biomarkers for Fabry disease in male and female adult patients revealed by proteomics.